Analisis Prosedur dan Kebijakan Pemberian Kredit Pada Koperasi CU Darma Harta Mumbul - I Kadek Semadi; Purnamawati, I Gusti Ayu (Universitas Pendidikan Ganesha, 2022)
This study aims to describe the procedures and policies for granting credit to the Darma Harta Mumbul CU cooperative. This type of research is descriptive qualitative. The data were collected by using interview, observation, and documentation methods, then the data that had been obtained were analyzed by descriptive analysis. The results of the research that have been carried out show that the procedures for granting credit at the CU Darma Harta cooperative are in line with the procedures for granting credit in general. Likewise, the credit policy applied to the CU Darma Harta cooperative has also been in line with the general lending policy. Procedures and policies for granting credit to CU Darma Harta cooperatives are able to minimize credit risk that may arise during the credit process. In addition, the procedures and policies for granting credit to the CU Darma Harta cooperative are also not difficult for members and also do not harm the cooperative.